Optimization of HPMC Aand Carbopol 940 Bases in the Formulation of Red Beet (Beta vulgaris L.) Gel Preparations as Hair Dye - Hartini, Putri Tri; Fauzi, Ziza Putri Aisyia; Utami, Dinda Sari; Karo-Karo, Sry Ulina; Puteri, Cut Intan Annisa (Journal of Pharmaceutical and Health Research, 2025)
Red beet (Beta vulgaris L.) is grass-shaped plant with short stems. Betacyianine is a red or purplish red pigment, while the betaxantin pigment has yellow colour and when diluted in water will form a red solution. This study aims to formulate hair dye gel with red beet juiceas colorant, evaluate the coloring capacity of the gel, and evaluate the stability of the formulation. 114.43 grams red beet juice was obtained using juicer, with yield percentage 55.76%. Phytochemical screening indicated alkaloid, tannin, flavonoid and saponin content. Hair dye gel is formulated in three different concentrations, F1 (10%), F2 (20%), F3 (30%) using combination of Carbopol 940 (0.5%) and HPMC (1%) as gel base. Hair dye gel obtained has beet distinctive smell. Evaluation results for the three-formulation showed that the color changed in all formulas. Color changing is influenced by pH degree of the formulation and temperature. The original color of the preparation only stable for 5 days, then the color changed due to oxidation at room temperature. Stability evaluation was conducted using Cycling Test method for 6 cycles in 12 days. All formula showed discoloration after 6 cycles from purple to brownish and they also showed viscosity change, F1 13673,34 cPs; F2 11826,67 cPs; dan F3 10673,34 cPs.